The Extent of Lymphadenectomy at the Time of Radical Cystectomy for Bladder Cancer and its Impact on Prognosis and Survival. (2005) - Josephson, David Y.; Stein, John P.
Abstract : Radical cystectomy has become a standard and effective treatment for muscle-invasive bladder cancer, however, the role and appropriate extent of a concomitant lymphadenectomy continues to evolve. We performed a detailed review of the English medical literature pertaining to the historical development and rationale for an extended lymphadenectomy in patients undergoing radical cystectomy. An historical perspective of lymphadenectomy and an anatomic account of bladder lymphatic drainage are presented. The boundaries and technique of an extended lymphadenectomy are also highlighted. Autopsy and contemporary survival data are presented to suggest that a more extensive lymphadenectomy has both prognostic and therapeutic utility. Furthermore, the stage of the primary bladder tumor, total number of lymph nodes removed, and the lymph node tumor burden are shown to be important prognostic variables in patients undergoing cystectomy with pathologic evidence of lymph node metastasis. Radical cystectomy provides not only excellent local cancer control with low pelvic recurrence rates, but also the best long-term survival. Radical cystectomy with an appropriate extended lymphadenectomy, while surgically more challenging, does not significantly increase the morbidity or mortality of the procedure. Although the absolute limits of the lymph node dissection remain to be determined, there is an evolving body of data to support that an extended lymphadenectomy provides further diagnostic and therapeutic benefit.